Estimation of critically ill patients' complaints by the nurse, the physician and the patient's family: A prospective comparative study. (December 2017) - Langlume, Sylvain; Labro, Guylaine; Puyraveau, Marc; Capellier, Gilles; Piton, Gaël
Abstract: Objectives: To evaluate the ability of the families of critically ill patients and of the intensive care team caring for the patient to communicate and accurately identify patients' complaints. Design: The complaints of critically ill patients were evaluated by a psychologist using a list of 12 items. The same day as the patient interview, the psychologist collected an estimation of the patient's complaints from the family, the nurse and the physician. Setting: 20-bed Intensive Care Unit in a large University Hospital. Main Outcome Measures: Patients' complaints. Results: 51 patients were included. The most frequently reported complaints were insomnia, the inability to talk and presence of a tracheal tube. Patients reported a significantly higher prevalence of "misunderstanding" than that estimated by the nurses (55% vs 33%, p = 0.045). The reported prevalence of "inability to talk" as the main complaint was significantly higher among patients than estimated by nurses and physicians (16% vs 2%, p = 0.03 and 16% vs 2%, p = 0.03 respectively). For the analysis of the individual complaints, there was a poor agreement between the patients and the other respondents. Conclusion: This study found that the estimation of critically ill patients' complaints by their families, nurses and physicians was largely suboptimal.